Nivolumab-induced new-onset seronegative rheumatoid arthritis in a patient with advanced metastatic melanoma: A case report and literature review - Haikal, Ammar; Borba, E; Khaja, Taqui; Doolittle, Gary; Schmidt, Paul (Avicenna Journal of Medicine, 2018)
Immune-related adverse events have been reported in patients treated with anti-programmed death-1 receptor drugs such as nivolumab. We present a case of a new-onset seronegative rheumatoid arthritis in a patient with metastatic melanoma treated with nivolumab.
Keywords: Immune-related adverse event; immunotherapy; inflammatory arthropathy; nivolumab; rheumatoid arthritis